Faktor-Faktor Pendorong Adopsi dan Potensi Ekonomi Biogas dari Limbah Ternak Sapi Perah di Hulu DAS Citarum - Febby Rizali Nur Rury; Akhmad Fauzi; Ahyar Ismail (Jurnal Manajemen Pembangunan Daerah, 2025)
ABSTRACT Dairy farming also produces manure as a by-product that has the potential to pollute the environment. Biogas from dairy waste is one of the solution to prevent pollution. However, some of the dairy farmers in the upstream Citarum watershed did not manage their waste and dispose it into the waterways. This study aims to identify factors that influence farmers' decisions to manage, stop managing or not managing dairy waste, and to estimate the potential costs and benefits of biogas processing. This study was conducted in February to August 2017 at Tarumajaya, Kertasari Sub-District of Bandung Regency. The method used was Multinomial Logistic Regression and Extended Cost-Benefit Analysis. The study showed that determinant factors that influence farmers’ tendency to manage dairy waste were fostering to the farmers (0,023), age (0,035), social pressure from the surrounding community (0,045), and membership in farmer groups (0,051). The Net-Present Value of biogas processing reached 5.298.340.449 IDR, and Net-B/C Ratio of 1,60. Keyword: dairy waste, biogas, multinomial logistic regression, extended CBA